(untitled) (Research, Society and Development, 2023)
The cultivation of vines is important for the economy of Brazil and Paraná. The production of common grape (Vitis labrusca L.) is part of the income of numerous families involved in the activity. And yet, it can be considered a diversification option for family farmers located in the Cantuquiriguaçu Region. Among the municipalities that comprise the region is Nova Laranjeiras. This municipality has its agricultural income mainly from temporary crops and cattle raising. Thus, in order to encourage the cultivation of a certain species, it is essential to know the implementation costs. Therefore, the objective of this research was to identify the costs of implantation of one hectare of vine cultivars Bordô, Niágara Branca and Rosada conducted in an espalier system in a property in the city of Nova Laranjeiras /PR. The study was carried out from February to May 2021. The total costs of implanting one hectare of vine reached R 109,872.10, whose most significant components in the cost composition were the expenses with inputs and materials, especially the costs with the driving system.